2007
DOI: 10.1111/j.1742-4658.2007.05755.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cardiac mitochondrial dysfunction by melatonin in septic mice

Abstract: Sepsis-induced multiple organ failure is the major cause of mortality in critically ill patients, and its incidence is rising [1]. The heart and cardiovascular systems are seriously affected during sepsis [2]. Although myocardial impairment in sepsis has been extensively studied, its etiology remains unclear [3]. Some reports The existence of an inducible mitochondrial nitric oxide synthase has been recently related to the nitrosative ⁄ oxidative damage and mitochondrial dysfunction that occurs during endotoxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 78 publications
5
144
1
Order By: Relevance
“…Moreover, inducible nitric oxide synthase (iNOS) induction during inflammation led to increased mitochondrial iNOS (i-mtNOS) enzyme activity, producing high levels of nitric oxide (NO Á ) responsible for the respiratory chain (RC) inhibition, ATP reduction Lopez et al 2006b), and mtDNA damage (Bartz et al 2011), all of them related to the severity of the inflammatory process (Brealey et al 2002). In these conditions, mitochondrial impairment produces ROS and RNS that in turn reduces mitochondrial bioenergetics, favoring cell damage and death (Escames et al 2007;Lopez et al 2006b). On the other hand, there are specific pathophysiological conditions directly derived from mtDNA mutations, causing chronic inflammatory diseases including neuromuscular and neurodegenerative disorders (Acuna et al 2011;DiMauro 2010;Muller et al 2010;Reddy 2008).…”
Section: Introduction: Inflammatory Clues and Mtdnamentioning
confidence: 99%
“…Moreover, inducible nitric oxide synthase (iNOS) induction during inflammation led to increased mitochondrial iNOS (i-mtNOS) enzyme activity, producing high levels of nitric oxide (NO Á ) responsible for the respiratory chain (RC) inhibition, ATP reduction Lopez et al 2006b), and mtDNA damage (Bartz et al 2011), all of them related to the severity of the inflammatory process (Brealey et al 2002). In these conditions, mitochondrial impairment produces ROS and RNS that in turn reduces mitochondrial bioenergetics, favoring cell damage and death (Escames et al 2007;Lopez et al 2006b). On the other hand, there are specific pathophysiological conditions directly derived from mtDNA mutations, causing chronic inflammatory diseases including neuromuscular and neurodegenerative disorders (Acuna et al 2011;DiMauro 2010;Muller et al 2010;Reddy 2008).…”
Section: Introduction: Inflammatory Clues and Mtdnamentioning
confidence: 99%
“…Mitochondrial impairment produces ROS and reactive nitrogen species (RNS) that in turn reduce mitochondrial bioenergetics, favoring cell damage and death [142,143]. Effectively, melatonin treatment significantly inhibits cholangiocarcinoma development [141].…”
Section: Function As a Free Radical Scavengermentioning
confidence: 99%
“…These findings prompted us to suggest that tissue dysoxia, which is characteristic of septic shock, is due to overproduction of NO, resulting in a mitochondrial defect with the consequent decrease in the extraction of O 2 by tissues, leading ultimately to multiple organ failure and death (Rees et al, 1998;Orsi et al, 2000b). In recent years, evidence in favour of this hypothesis has been accumulating, including the demonstration of a significant mitochondrial defect in biopsies of skeletal muscle of individuals with sepsis (Brealey et al, 2002), the observation of an NO-dependent defect in complex I of biopsies obtained from animals with septic shock (Protti et al, 2007) and the preservation of mitochondrial activity in a septic shock model in inducible nitric oxide synthase (iNOS) knockout mice (Escames et al, 2007). As NO, which is produced in large quantities by iNOS, is also known to be involved in localized acute and/or chronic inflammatory and degenerative disorders, we suggested that a similar mitochondrial defect to that observed in septic shock is likely to occur in such conditions (Moncada and Erusalimsky, 2002).…”
Section: Introductionmentioning
confidence: 99%